Influence Of Certain Thermo-Physical Properties On Prandtl Number Of Water Based Nanofluids - Azmi, W. H.; Sharma, K. V. (2010)

(untitled)
The thermo physical properties such as thermal conductivity, viscosity, density and specific heat are essential for the determination of nanofluid heat transfer coefficients. Experimental data indicate the nanofluid thermal conductivity to increase with temperature and decrease with particle size. However, viscosity is observed to decrease with temperature and increase with particle size. This opposing nature of the two properties along with the nanofluid specific heat which decreases with both temperature and particle size have a significant influence on the values of nanofluid Prandtl number. The forced convective heat transfer coefficients are dependent on Reynolds and Prandtl numbers which in turn are dependent on the nanofluid properties. Regression equations have been developed as a function of concentration, temperature and particle size using the experimental data available in literature useful in the estimation of convective heat transfer coefficients. The analyses of these parameters indicate that the nanofluid heat transfer coefficient need not necessarily predict higher values of heat transfer coefficients when compared with water at all concentrations, contrary to the general expectations. The condition for heat transfer enhancement is explained.